Protected Culture for Vegetable and Small Fruit Crops: High Tunnels for Strawberry Production in Florida - Bielinski M. Santos; Teresa P. Salamé-Donoso; Craig K. Chandler; Steven A. Sargent (EDIS, 2010)
HS1162, a 4-page illustrated fact sheet by Bielinski M. Santos, Teresa P. Salamé-Donoso, Craig K. Chandler, and Steven A. Sargent, presents the results of research comparing the effects of high-tunnel and open-field production on the growth, fruit earliness, and yield of strawberry cultivars in Florida. Published by the UF Department of Horticultural Sciences, March 2010.